Information, credit, and organization - José María Liberti; Amit Seru; Vikrant Vig (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2015)
This paper investigates the effect of a change in informational environment of borrowers on the orga- nizational design of bank lending. We use micro-data from a large multinational bank and exploit the sudden introduction of a credit registry, an information-sharing mechanism across banks, for a subset of borrowers. Using within borrower and loan officer variation in a difference-in-difference empirical de- sign, we show that expansion of credit registry led to an improvement in allocation of credit to affected borrowers. There was a concurrent change in the organizational structure of the bank that involved a dramatic increase in delegation of lending decisions of affected borrowers to loan officers. We also find a significant expansion in scope of activities of loan officers who deal primarily with affected borrow- ers, as well as of their superiors. There is suggestive evidence that larger banks in the economy were better able to implement similar changes as our bank. We argue that these patterns can be understood within the framework of incentive-based and information cost processing theories. Our findings could help rationalize why improvements in the information environment of borrowers may be altering the landscape of lending by moving decisions outside the boundaries of financial intermediaries.
urn:nbn:de:hebis:30:3-382892
Keywords: 330